Reconnaissance survey of the human-elephant conflict situation around Dadieso area in western Ghana - Sam, Moses; Ayesu, Samuel; Kumordzi, Bright; Wilson, Sandra (Pachyderm, 2003)
Elephant no longer frequent the Dadieso area in western Ghana in the numbers or range area they did up to about 1957. No evidence of their presence was noted in Dadieso or Disue River FR's, however until recently they were observed in the region to the south of the Disue River FR. Questionnaire completed during interviews in 14 villages in the vicinity of the two forest reserves indicated that elephants which were present in area preferred crops of plantain, cassava, cocoa, oil palm, cocoyam and yam. No crop raiding occurred since 2000, prior to that it was not as extensive as the conflict around Kakum NP or the Red Volta Valley region. The particualar project was undertaken as part of a wildlife/forest student training course. (Ayesu. 2003)